ENZYME ACTIVITY OF LIGNOLYTIC BACTERIA ISOLATED FROM EARTHWORM ON WEEDS CROPS SUBSTRATES - I W., Wijana; Mudita, I M. (Jurnal Peternakan Tropika, 2017)
Evaluation of enzyme activity by eight lignolytic bacteria isolated from earthworm ( Lumbricus rubellus ) on weeds crops  especially water hyacint and water lettuc e leaves had been carried out for have the best lignolytic bacteria as weeds crops degrader. The experiment was conducted with completely randomized design (CRD) 8 treatments and 3 replications, treatments based on the eight cellulolignolytic bacteria isolates coded EB 1 LG, EB 2 LG, EB 3 LG, EB 4 LG, EB 5 LG, EB 6 LG, EB 7 LG and EB 8 LG. Lignase enzyme activity measured on 4 (four) incubation time periods were 10; 20; 30 and 60 menute using vanillin callibration curve was Y = 0,00635 X + 0,21098 (r 2 = 0,89). The results showed that lignolytic bacteria isolated from earthworm coded EB3LG have highest and significantly (P<0,05) enzyme activity on water hyacinth substrates were 0,448 IU, 0,269 IU, 0,201 IU and 0,110 IU on incubation time periods respectively, while bacteria isolates coded EB1LG have highest (P<0,05) enzyme activity on water lettuce leaves were 0,586 IU; 0,346 IU; 0,248 IU and 0,130 IU, and both significant different with bacteria isolates coded EB8LG. Based on this study concluded that lignolytic bacteria isolates coded EB1LG and EB3LG were excellent bacteria isolates degrader weeds crops especially the water hyacinth and water lettuce leaves than the other isolates. Key words: Cellulolytic Bacteria, Earthworm, Ability on degrading substrates, Weed Crops